Sexual Orientation Disparities in Preventable Disease: A Fundamental Cause Perspective - Richard Bränström; Mark L. Hatzenbuehler; John E. Pachankis; Bruce G. Link (2016)
Objectives. To determine whether fundamental cause theory (which posits that, in societal conditions of unequal power and resources, members of higher-status groups experience better health than members of lower-status groups because of their disproportionate access to health-protective factors) might be relevant in explaining health disparities related to sexual orientation. Methods. We used 2001 to 2011 morbidity data from the Stockholm Public Health Cohort, a representative general population–based study in Sweden. A total of 66 604 (92.0%) individuals identified as heterosexual, 848 (1.2%) as homosexual, and 806 (1.1%) as bisexual. To test fundamental cause theory, we classified diseases in terms of preventability potential (low vs high). Results. There were no sexual orientation differences in morbidity from low-preventable diseases. By contrast, gay or bisexual men (adjusted odds ratio [OR] = 1.48; 95% confidence interval [CI] = 1.13, 1.93) and lesbian or bisexual women (adjusted OR = 1.64; 95% CI = 1.28, 2.10) had a greater risk of high-preventable morbidity than heterosexual men and women, respectively. These differences were sustained in analyses adjusted for covariates. Conclusions. Our findings support fundamental cause theory and suggest that unequal distribution of health-protective resources, including knowledge, prestige, power, and supportive social connections, might explain sexual orientation health disparities.